Proteasome inhibition slightly improves cardiac function in mice with hypertrophic cardiomyopathy - Schlossarek, Saskia; Singh, Sonia R.; Geertz, Birgit; Schulz, Herbert; Reischmann, Silke; Hübner, Norbert; Carrier, Lucie (Frontiers in Physiology, 2014)
A growing line of evidence indicates dysfunctional ubiquitin-proteasome system (UPS) in cardiac diseases. Anti-hypertrophic effects and improved cardiac function have been reported after treatment with proteasome inhibitors in experimental models of cardiac hypertrophy. Here we tested whether proteasome inhibition could also reverse the disease phenotype in a genetically-modified mouse model of hypertrophic cardiomyopathy (HCM), which carries a mutation in Mybpc3, encoding the myofilament protein cardiac myosin-binding protein C. At 7 weeks of age, homozygous mice (KI) have +39% higher left ventricular mass and -29% lower fractional area shortening (FAS) than wild-type (WT) mice. Both groups were treated with epoxomicin (0.5 mg/kg/day) or vehicle for 1 week via osmotic minipumps. Epoxomicin inhibited the chymotrypsin-like activity by ~50% in both groups. All parameters of cardiac hypertrophy (including the fetal gene program) were not affected by epoxomicin treatment in both groups. In contrast, FAS was +12% and 35% higher in epoxomicin-treated than vehicle-treated WT and KI mice, respectively. To identify which genes or pathways could be involved in this positive effect, we performed a transcriptome analysis in KI and WT neonatal cardiac myocytes, treated or not with the proteasome inhibitor MG132 (1 µM, 24 h). This revealed 103 genes (4-fold difference; 5% FDR) which are commonly regulated in both KI and WT cardiac myocytes. Thus, even in genetically-modified mice with manifest HCM, proteasome inhibition showed beneficial effects, at least with regard to cardiac function. Targeting the UPS in cardiac diseases remains therefore a therapeutic option.